(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to prepare an educational program according to the modeling strategy and to reveal its effect on acquiring the art of performing some wrestling skills for third stage students. To achieve this goal, the researchers developed and designed an educational program using a modeling strategy. The researchers adopted the experimental method. The sample was identified as (36) students from the third stage in the College of Physical Education and Sports Sciences / University of Mosul for the academic year (2018-2019), They were divided into two equal experimental and control groups (age, height, weight, and physical fitness components). Each group consisted of (18) students. The experimental group was studied according to the modeling strategy. As for the control group, it was taught in the usual way, after which the research experiment was applied for a period of four weeks and at one unit per week for each group, after which the post-tests were conducted. The SPSS statistical system was used for data processing and analysis. The result was that the experimental group that was studied according to the modeling strategy outperformed the control group in the skill acquisition of the skills of concerned with the study. The researchers recommended emphasizing the use of a modeling strategy in teaching wrestling subjects to third-stage students